Experimental characterization of a fully polarimetric pulsed terahertz spectroscopy system - Gurjar, Nikita; Ware, Morgan E.; El-Shenawee, Magda (Frontiers in Physics, 2024)
A terahertz time domain pulsed spectroscopy system is modified to provide fully polarimetric radiation and analysis. The operation of this polarimetry system is characterized using a birefringent, x-cut quartz crystal. The modification is based on rotating the photoconductive antennas such that both the emitted and detected polarizations are out of the plane of incidence. Subsequently, broadband wire grid polarizers are used to select the incident and detected direction of linear polarization to be either parallel with (vertical) or perpendicular to (horizontal) the plane of incidence with the sample surface. The experiments are conducted in both transmission and reflection. Depending on the frequency, the phase retardation of the incoming electric field components along the two perpendicular optical axes of the quartz crystal changes differently. This results in the polarization of the light exiting the crystal changing with frequency. As a result, multiple frequencies are identified where the crystal behaves as a near ideal quarter-, half-, or full-wave retarder. Additionally, due to the time-domain nature of the experiment, transmitted and reflected electric fields are measured after multiple consecutive reflections within the crystal. This leads to a further, complex control over the final polarization state of the signal. Finally, images of a resolution standard are obtained demonstrating the characteristics of the polarimetry system.